Down-staging of obesity one year after bariatric surgery: a new proposal of Edmonton obesity staging system - Quinto, Giulia; Bettini, Silvia; Neunhaeuserer, Daniel; Battista, Francesca; Milan, Gabriella; Gasperetti, Andrea; Vecchiato, Marco; Vettor, Roberto; Ermolao, Andrea; Busetto, Luca (Frontiers in Endocrinology, 2023)
Background: Different approaches are used to classify obesity severity. The Edmonton Obesity Staging System (EOSS) considers medical, physical and psychological parameters. A new modified EOSS with a different functional evaluation method, measuring Cardiorespiratory Fitness (CRF), has been recently proposed, EOSS-CRF. Bariatric surgery (BS) is one of the most efficient treatments of obesity and all aspect of related disorders. No studies have yet applied EOSS-CRF after BS. Therefore, the aim of this study was to evaluate modifications in EOSS and EOSS-CRF before and after BS. Methods: This observational study finally enrolled 72 patients affected by obesity. A multi-disciplinary assessment in order to evaluate eligibility to surgical treatment has been performed, including anamnesis, physical evaluation, anthropometric data measurement, biochemical blood exams and cardiopulmonary exercise testing. One year after BS the same protocol were applied. Patients have been classified according to EOSS and EOSS-CRF before and one year after BS. Results: After BS, patients categorized in classes associated to severe obesity (EOSS 2 or EOSS-CRF 2) reduced significantly. Using EOSS, patients without functional impairment were 61% before surgery and 69% after BS (p=0.383). Using EOSS-CRF, patients considered without functional impairment were only 9.7% before BS; this percentage significantly raised to 50% after BS (p<0.001). The impact of functional domains before and after BS is different in grading patients in EOSS and EOSS-CRF, respectively. Conclusions: Improvements obtained after BS are adequately summarized by EOSS and EOSS-CRF. The EOSS-CRF grading method for functional impairment seems to better reflect the known amelioration obtained after BS. Objective measurements of CRF may provide additional value to classify severity of obesity, also in the follow-up after BS.